FOUNDATIONS OF PROFESSIONAL DEVELOPMENT OF FUTURE ENGLISH LANGUAGE TEACHERS - Murodova Jasmina Jamshid qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article discusses the professional development of future English language teachers and its importance in education. It highlights the teacher’s role not only as a knowledge provider but also as a guide in students’ development. The importance of pedagogical knowledge, methodology, and communication skills is also emphasized.